Meningkatkan kualitas air masyarakat Desa Aka-Akae Kecamatan Watang Sidenreng Kabupaten Sidrap - Ishak Ishak; Mohammad Junaedi Rahman (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Aka-akae Village, Watang Sidenreng Subdistrict, Sidrap Regency has the potential for adequate water and agricultural resources. Agricultural products include abundant crops and vegetables. However, this condition does not make the villagers become healthier and more prosperous. The problems faced are: 1) The quality of water consumed by the community is still low, 2) The lack of technology used by the community in treating water and utilizing existing local potential, 3) The lack of knowledge about entrepreneurship. Departing from this condition, the KKN-PPM was agreed to be implemented in 2019. The main program was the application of appropriate technology for water purification systems, processing of food crops into fast food, and entrepreneurship training. So, with this KKN-PPM expected to improve water quality, the growth of the entrepreneurial groups in agriculture and community income will increase. Expected outputs are (1) the availability of a simple water purification system for each community member, 2) the availability of processed agriculture products such as spinach chips and mustard greens (3) the creation of entrepreneurial groups. Thus it is expected that the quality of life of the people in Watang Sidenreng Sub-district can improve including community income.